Sustainable Engineering-Based Management and Valorization of Seaweed Waste for High-Value Biomass Utilization - Yuhendra AP; Reza Kusuma Nurrohman; Mi’raj Fuadi; Satrijo Saloko; Rahmat Sabani; I Wayan Sweca Yasa; Joko Sumarsono; Setyaning Pawestri; Nur Afni; Qabul Dinanta Utama; Wiharyani Werdiningsih; Sukmawaty Sukmawaty; Guyup Mahardhian Dwi Putra; Diah Ajeng Setiawati; Surya Abdul Muttalib; Made Gendis Putri Pertiwi; Isnaini Puspitasari; Fakhrul Irfan Khalil; Fuad Sauqi Isnain; Endang Purnama Dewi; Elya Antariksana Bachmida; Wan Rosli Bin Wan Ishak; Haslina Ahmad (Universitas Mataram, 2026)
This community service initiative focused on the sustainable management and valorization of Kappaphycus alvarezii waste in Ekas Buana Village, specifically within the Merah Putih Fishing Camp engaging local fishermen from Paser Puteh, under the leadership of Mr. M. Toni. This initiative, coordinated by Fatepa and led by Dr. Reza Kusuma Nurrohman, was conducted on January 22, 2026, and featured contributions from notable experts including Prof. Wan Rosli Bin Wan Ishak from Universiti Sains Malaysia and Assoc. Prof. ChM. Dr. Haslina Ahmad from Universiti Putra Malaysia. The discussions included the potential of K. alvarezii as a sustainable source of bioactive compounds for functional food innovation, emphasizing riboflavin extracts and their health benefits. This initiative aimed at uplifting local fishing communities by demonstrating the economic viability of seaweed waste and its integration into sustainable agricultural practices. The findings align with cooperative strategies fostering dual benefits: environmental sustainability through waste valorization and economic advancement through the creation of high-value products.